Proyecto de factibilidad para la implementación de una empresa comercializadora de arroz macareño al natural en la ciudad de Loja - Honores Calva, Tyrone Maciel (2020)
Being aware that the rice sector of the province of Loja produces 24% of the national rice production and that it has a yield of 9.54 tons per hectare, and that despite this it presents needs, the idea of participating in the sector is born Agricultural economics of the Macará canton presenting a proposal that allows to give economic stability to the members of this rice sector, since many times they cannot compete against the entry of foreign products and the large commercializes, with the development of this project proposes the acquisition of rice from small producers without generating expenses towards their economy, this will allow their profitability to be greater, boosting the sector. The development of this research begins with the market study, resulting in 64% of the commercialists in Loja buying natural macareño rice, in the same way a per capita consumption of 144qq of rice per micro market was established with an average price of US $ 43 per quintal, it was also determined that 88.89% of the micro markets would be willing to acquire the product of the new marketer. After this study, we proceeded with the development of the technical study which allowed us to determine size, installed capacity, capacity used, project engineering, macro and micro location, process flow and the location of the commercialization company. Regarding the Administrative Organization, the legal constitution is presented, opting for the option of a Limited Liability Sole Company, being the one that presents the best benefits, in addition to presenting a manual of functions and three diagrams, in the same way the five hierarchical levels are established as structural organization In the economic study, a study of the financial indicators VAN, TIR, PRC, RBC, breakeven point and sensitivity analysis was prepared, after its application it was determined that the project is feasible, but in the first 3 years it will maintain a percentage Low utility since it is at a time of introduction to the market, that is why its implementation is recommended to provide an economic, social and productive contribution to the entire rice sector of the Macará canton.